2012
DOI: 10.1016/j.bjid.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B surface antigen and its correlation with risk factors among new recruits in Turkey

Abstract: The HBsAg seropositivity found in this study supports the fact that Turkey remains in the medium endemicity zone, and that horizontal transmission is predominant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
3
11
0
1
Order By: Relevance
“…anti-HBs (31.9%) seroprevalence fall within the ranges provided for countries with an intermediate endemic profile (4,20) and in agreement with past studies on epidemiology of hepatitis in Turkey which indicated an overall prevalence of chronic HBV infection of 4-10 % (3.5% in the western and 7% in the eastern regions), and of anti-HBs positivity of 20.6-52.3% [7,10,14,15,19,21,22]. This regional difference in HBV positivity, not observed in HCV infection, re-emphasizes the role of close contact and intrafamilial transmission in areas with crowded families and poor hygienic conditions in HBV seroprevalence.…”
Section: Discussionsupporting
confidence: 89%
“…anti-HBs (31.9%) seroprevalence fall within the ranges provided for countries with an intermediate endemic profile (4,20) and in agreement with past studies on epidemiology of hepatitis in Turkey which indicated an overall prevalence of chronic HBV infection of 4-10 % (3.5% in the western and 7% in the eastern regions), and of anti-HBs positivity of 20.6-52.3% [7,10,14,15,19,21,22]. This regional difference in HBV positivity, not observed in HCV infection, re-emphasizes the role of close contact and intrafamilial transmission in areas with crowded families and poor hygienic conditions in HBV seroprevalence.…”
Section: Discussionsupporting
confidence: 89%
“…In Turkey, hepatitis B vaccine was included in the national vaccination program in 1998. While the vaccine is given to any adult in the risk groups who desires protection, all infants are vaccinated with three doses (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, hepatitis B vaccination was included in the national immunization program in 1998, and infants have been vaccinated with three doses. Adults in the risk groups are also vaccinated at their request (16,17).…”
Section: Discussionmentioning
confidence: 99%